2021
DOI: 10.1021/acsami.1c04514
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Rich Anti-perovskite Li2OHBr-Based Polymer Electrolytes Enabling an Improved Interfacial Stability with a Three-Dimensional-Structured Lithium Metal Anode in All-Solid-State Batteries

Abstract: All-solid-state lithium-metal batteries, with their high energy density and high-level safety, are promising next-generation energy storage devices. Their current performance is however compromised by lithium dendrite formation. Although using 3D-structured metal-based electrode materials as hosts to store lithium metal has the potential to suppress the lithium dendrite growth by providing a high surface area with lithiophilic sites, their rigid and ragged interface with solid-state electrolytes is detrimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Anti-perovskites (Li 2 OHX, where X = Cl, Br, F) are a specific type of anti-perovskite solid electrolyte that have high ionic conductivities, low-temperature processability, and a high electrochemical stability window [118]. Recent studies have shown that Li-rich anti-perovskite Li 2 OHBrbased PEs can be utilized as a flexible SSE to promote the performance of batteries [119]. Anti-perovskite electrolytes are excellent options for use in SSBs due to their structural flexibility and tunability [120].…”
Section: Oxidebasedmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-perovskites (Li 2 OHX, where X = Cl, Br, F) are a specific type of anti-perovskite solid electrolyte that have high ionic conductivities, low-temperature processability, and a high electrochemical stability window [118]. Recent studies have shown that Li-rich anti-perovskite Li 2 OHBrbased PEs can be utilized as a flexible SSE to promote the performance of batteries [119]. Anti-perovskite electrolytes are excellent options for use in SSBs due to their structural flexibility and tunability [120].…”
Section: Oxidebasedmentioning
confidence: 99%
“…ies [119]. Anti-perovskite electrolytes are excellent options for use in SSBs due to their structural flexibility and tunability [120].…”
Section: Oxidebasedmentioning
confidence: 99%
“…Li composites and Li hosted in a 3D structure are different strategies to inhibit the generation of dendrites. [163][164][165] The reasons for using Li alloys and Li compounds as anodes for SSBs are as follows: (1) this type of compound has a smaller nucleation overpotential which makes it easier to induce lithium nucleation and precipitation. (2) It is lithiophilic and induces uniform deposition of lithium.…”
Section: Metal Anode Modificationmentioning
confidence: 99%
“…By replacing the flammable liquid electrolyte with nonflammable solid electrolytes (SEs), all‐solid‐state Li metal batteries (ASSLMBs) are considered as safer alternatives for energy storage compared with the commercial Li‐ion batteries. [ 1–13 ] Among the reported families of SEs, Li‐rich antiperovskite (LiRAP) SEs (e.g., Li 3 OCl) possess the advantages of high Li ion conductivity (10 −3 S cm −1 ), low activation energy (<0.3 eV), wide electrochemical window, light weight, low cost, and low toxicity, [ 14–21 ] which show great promises for practical applications. They have a similar crystal structure to the conventional perovskites but with electronically inverted lattice sites.…”
Section: Introductionmentioning
confidence: 99%
“…
storage compared with the commercial Li-ion batteries. [1][2][3][4][5][6][7][8][9][10][11][12][13] Among the reported families of SEs, Li-rich antiperovskite (LiRAP) SEs (e.g., Li 3 OCl) possess the advantages of high Li ion conductivity (10 −3 S cm −1 ), low activation energy (<0.3 eV), wide electrochemical window, light weight, low cost, and low toxicity, [14][15][16][17][18][19][20][21] which show great promises for practical applications. They have a similar crystal structure to the conventional perovskites but with electronically inverted lattice sites.
…”
mentioning
confidence: 99%